Dis(en)abled: legitimating discriminatory practice in the name of inclusion?. (March 2016) - Atkins, Liz
Abstract : This article explores tensions between the policies and practice of inclusion and the lived experiences of disabled young people in education. Drawing on the narratives of two young men who participated in a small pilot study, it utilises theoretical concepts related to disability, structure and agency, and power and control, as it explores the ways in which inclusion can create subtle (and sometimes not so subtle) forms of exclusion. Focusing on the young men's experiences of further and higher education, it is argued that inclusive practices and policies, however well intentioned, can create new and subtle forms of marginalisation through the structures and discourse intended to address exclusion. I conclude by questioning whether, in a diverse and disparate society, in which all our lives are defined by the extent to which we are more or less equal than others, inclusion can ever be anything other than an illusory concept.